PEMBELAJARAN BERBASIS MAINAN TERHADAP KEMAMPUAN BERPIKIR KREATIF ANAK USIA DINI - Ramadhani, Anderi Putri; Hamel, Arin Auliani; Pratiwi, Dini Putri; Shafira, Nadia; Pratiwi, Rika Luthfia; Ruhiyat, Silvani; Widjayatri, RR. Deni (Journal of Early Childhood Education (JECE), 2023)
Eaery child has innate abilities, one of which is creative thinking. Creative thinking is a stage that can be utilized by young children to solve problems they face. Stimulating children to develop creative thinking involves channeling their ideas through play activities, making them trained to develop their creative thinking abilities and learn to solve problems they encounter. The purpose of this study is to investigate the effect of play-based learning on the creative thinking abilities of young children. The research method used is Systematic Literature Review (SLR). The results show that through play activities, children can create various creations based on their own ideas or thoughts, which are then applied through games. With creative thinking abilities, children also become trained and accustomed to solving problems they face. Play-based learning is proven to enhance creative thinking abilities in young children. The conclusion of this study is that play-based learning can enhance the creative thinking abilities of young children. Various types of games such as Loose Parts Play, playing with playdough, and